„Cinemagraphs” Jamie Beck w kontekście dramatycznej teorii literatury - Woźniak, Ewelina (Wydawnictwo Naukowe UAM w Poznaniu, 2012)
The purpose of this article is to present works of a New York photographer Jamie Beck, who developed a new type of moving photography – cinemagraphs, and look at her work from the perspective of the dramatic theory of literature. Jamie Beck in her works redefines many notions related to the visual realm. Movement and time relationship, the model identity and the impact of material on the image perception are the most interesting problems, that are connected with cinemagraphs. All these issues are analyzed in relation to fields dealing with image: André Rouille’s and Roland Barthes’ photographic theories, art history represented by Georges Didi- Huberman and Rudolf Arnheim’s “the psychology of creative eye”.
Jamie Beck’s “Cinemagraphs” in the context of dramatic theory of literature